Stellar Mass Calibrations for Local Low-mass Galaxies - Mithi A. C. de los Reyes; Yasmeen Asali; Risa H. Wechsler; Marla Geha; Yao-Yuan Mao; Erin Kado-Fong; Ragadeepika Pucha; William Grant; Pratik J. Gandhi; Viraj Manwadkar; Anna Engelhardt; Ferah Munshi; et al. (The Astrophysical Journal)
The stellar masses of galaxies are measured from integrated light via several methods—however, few of these methods were designed for low-mass ( M _⋆ ≲ 10 ^8 M _⊙ ) “dwarf” galaxies, whose properties (e.g., stochastic star formation, low metallicity) pose unique challenges for estimating stellar masses. In this work, we quantify the precision and accuracy at which stellar masses of low-mass galaxies can be recovered using UV/optical/IR photometry. We use mock observations of 469 low-mass galaxies from a variety of models, including both semi-empirical models (GRUMPY and UniverseMachine-SAGA) and cosmological baryonic zoom-in simulations (MARVELous Dwarfs and FIRE-2), to test literature color– M _⋆ / L relations and multiwavelength spectral energy distribution (SED) mass estimators. We identify a list of “best practices” for measuring stellar masses of low-mass galaxies from integrated photometry. We find that literature color– M _⋆ / L relations are often unable to capture the bursty star formation histories (SFHs) of low-mass galaxies, and we develop an updated prescription for stellar mass based on g − r color that is better able to recover stellar masses for the bursty low-mass galaxies in our sample (with ∼0.1 dex precision). SED fitting can also precisely recover stellar masses of low-mass galaxies, but this requires thoughtful choices about the form of the assumed SFH: Parametric SFHs can underestimate stellar mass by as much as ∼0.4 dex, while nonparametric SFHs recover true stellar masses with insignificant offset (−0.03 ± 0.11 dex). Finally, we also caution that noninformative (wide) dust attenuation priors may introduce M _⋆ uncertainties of up to ∼0.6 dex.